Small and Medium Size Enterprises in Nigeria: Problems and Prospects - Abdullahi, Muhammad Muktar (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The role of small and medium enterprises (SMEs) in economic development is undebatable. Therefore, identifying SMEs’ problems and finding solutions for these problems are vital for economic development and growth in Nigeria. With a 173.6 million of population, Nigeria is a highly populated low income country where a significant portion of it’s population is currently facing poverty. This is partly due to the inability of SMEs in creating jobs and employment in Nigeria. This thesis investigates the primary problems of SMEs in Nigeria through a survey study of SMEs in two major cities. The survey findings indicated that several reasons attributed to the limited contribution of SMEs to employment and economic growth. The most important of these problems are identified as the infrastructural weaknesses, limited access to finance, and the uncertainties in the economy are the most important problems of SMEs in Africa. Keywords: SMEs, economic development, poverty, Nijeria, access to fınance, weak infrastructure.

ÖZ: Küçük ve orta büyüklükteki işletmelerin (KOBİ’lerin) ekonomik büyüme için önemi inkar edilemez. Bu nedenle KOBİ’lerin sorunlarını saptayıp bu sorunlara çözüm üretmek ülkelerin ekonomik büyümesi ve gelişmesi için son derece önemlidir. 173. 6 milyon nifusuyla Nijerya Afrika’ın en kalabalık nifusuna sahip olan ülkelerinden birisidir ve bu nifusun büyük bir oranı yoksuldur. Bu yoksulluğun nedeni, kısmen, KOBİ’lerin yeterince gelişmemesi ve beklenen derecede iş yaratmamasıdır. Bu tez, Nijerya’ nın iki önemli şehrinde bir anket çalışması uygulayarak Nijerya’da KOBİ’lerin en önemli sorunlarını saptamaya çalışmaktadır. Anket bulguları Nijerya’da KOBİ’lerin iş yaratma ve ekonomiye olan katkılarını büyük ölçüde engellenyen birden fazla faktör olduğunu saptamıştır. Önemine göre bu faktörler şöyle sıralanabilir; altyapı eksikliği, ekonomideki belirsizlik, krediye ulaşmada zorluklar. Anahtar kelimeler: KOBİ’ler, ekonomid gelişme, yoksulluk, Nijerya, krediye ulaşım, altyapı eksikliği.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2015. Supervisor: Prof. Dr. Hatice Jenkins.
Keywords: Banking and Finance; Small and Medium Size Enterprises-Business-Nigeria; SMEs; economic development; poverty; Nijeria; access to fınance; weak infrastructure